GTF2IRD1 on chromosome 7 is a novel oncogene regulating the tumor‐suppressor gene TGFβR2 in colorectal cancer. Issue 2 (27th December 2019) - Nambara, Sho; Masuda, Takaaki; Kobayashi, Yuta; Sato, Kuniaki; Tobo, Taro; Koike, Kensuke; Noda, Miwa; Ogawa, Yushi; Kuroda, Yousuke; Ito, Shuhei; Eguchi, Hidetoshi; Sugimachi, Keishi; et al.
Abstract: Chromosome 7q (Ch.7q) is clonally amplified in colorectal cancer (CRC). We aimed to identify oncogenes on Ch.7q that are overexpressed through DNA copy number amplification and determine the biological and clinical significance of these oncogenes in CRC. We identified general transcription factor 2I repeat domain‐containing protein 1 ( GTF2IRD1 ) as a potential oncogene using a CRC dataset from The Cancer Genome Atlas with a bioinformatics approach. We measured the expression of GTF2IRD1 in 98 patients with CRC using immunohistochemistry and RT‐quantitative PCR (RT‐qPCR). The biological effects of GTF2IRD1 expression were explored by gene set enrichment analysis (GSEA). Next, we undertook in vitro cell proliferation and cell cycle assays using si GTF2IRD1 ‐transfected CRC cells. We further investigated the oncogenic mechanisms through which GTF2IRD1 promoted CRC progression. Finally, we assessed the clinical significance of GTF2IRD1 expression by RT‐qPCR. GTF2IRD1 was overexpressed in tumor cells and liver metastatic lesions. The GSEA revealed a positive correlation between GTF2IRD1 expression and cell cycle progression‐related genes. GTF2IRD1 knockdown inhibited cell proliferation and induced cell cycle arrest in Smad4 ‐mutated CRC. GTF2IRD1 downregulated the expression of the gene encoding transforming growth factor β receptor 2 ( TGFβR2 ), a tumor‐suppressor gene in Smad4 ‐mutated CRC. On multivariate analysis, high GTF2IRD1 expression was an independent poor prognostic factor. Clinicopathological analysis showed that GTF2IRD1 expression was positively correlated with liver metastasis. In conclusion, GTF2IRD1 promoted CRC progression by downregulating TGFβR2 and could be a prognostic biomarker on Ch.7q in CRC. GTF2IRD1 could also be a novel oncogene in CRC. Abstract : GTF2IRD1 is identified as a driver gene on chromosome 7q of colorectal cancer (CRC). GTF2IRD1 promotes cell cycle progression by downregulation of TGFβR2, and GTF2IRD1 could be a novel oncogene in Smad4 ‐mutated CRC.